Mercury capture on a supported chlorocuprate(ii) ionic liquid adsorbent studied using operando synchrotron X-ray absorption spectroscopy. Issue 47 (15th November 2016) - Boada, Roberto; Cibin, Giannantonio; Coleman, Fergal; Diaz-Moreno, Sofia; Gianolio, Diego; Hardacre, Christopher; Hayama, Shusaku; Holbrey, John D.; Ramli, Rafin; Seddon, Kenneth R.; Srinivasan, Geetha; Swadźba-Kwaśny, Małgorzata
Abstract : Oxidation and comproportionation mechanisms for mercury capture are identified. Abstract : Mercury scrubbing from gas streams using a supported 1-butyl-3-methylimidazolium chlorocuprate(ii ) ionic liquid ([C4 mim]2 [Cu2 Cl6 ]) has been studied using operando EXAFS. Initial oxidative capture as [HgCl3 ] − anions was confirmed, this was then followed by the unanticipated generation of mercury(i ) chloride through comproportionation with additional mercury from the gas stream. Combining these two mechanisms leads to net one electron oxidative extraction of mercury from the gas with increased potential capacity and efficiency for supported ionic liquid mercury scrubbers.